Islamic vs. Conventional Equity Indices and Investor Sentiments - Ume Habibah; Suresh Kumar Oad Rajput; Muhammad Shahid İqbal (Türkiye İslam İktisadı Dergisi)
Purpose: This paper aims to empirically investigate the equity-sentiment relationship along with making a comparison between the Islamic equity indices with conventional ones.